GERAKAN MASSA PASCA PENDUDUKAN AMERIKA DI JEPANG - Rafiqa Nur’aini Al Hakim Nur’aini Al Hakim (Fakultas Ilmu Budaya universitas Hasanuddin, 2019)
This paper will discuss about the mass movement that was held in Japan in 1945 after World War II to the 1970s when the Vietnam War issue arose. The period which was very important for the Japanese people at that time determined their vision and mission after being defeated in World War II which led to pacifism or anti-war. The mass movement carried out by the Japanese people at that time was included in the phenomenon of democracy which was inseparable from the American occupation at that time. This paper was published using the Rikkyo campus newspaper in 1954-1967 and also books and journals used as historical information. With this writing, it is hoped that the reader will become more aware of Japanese society in 1945 through the 1970s as was the mass movement that occurred at that time. Keywords: Japanese mass movement, pacifism, democracy